Language Learning Within an EAP Framework - Md Nordin, Shahrina; Chong, Su Li (MELTA (Malaysian English Language Teaching Association), 2003)
This paper is premised on the English for Academic Purposes approach whereby language learning is contextualised within the learners’ domains of study. A study involving 20 students examined the ‘discourse organization’ during group presentations and other class activities. The findings of this study lend support to the EAP approach, which makes the language learning experience more relevant and meaningful, thereby increasing the learners’ motivation.